Environmental geochemistry : site characterization, data analysis and case histories - De Vivo, B. (Benedetto); Belkin, H. E.; Lima, Annamaria (Elsevier, 2018)
This book reviews the role of geochemistry in the environment and details state-of-the-art field applications, specifically in pollution and remediation situations. Chapters cover philosophy, procedures, applications, health problems related to environment pollution, waste disposal, and data base management, and includes case histories.